Pengaruh Kualitas Produk dan Perceived Value Terhadap Kepuasan Pelanggan Smartphone Samsung di Kota Bandung - Minda Wulandari; Ida Farida Oesman (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
The goal of this study is to ascertain how customer satisfaction among Samsung smartphone users in Bandung is influenced by product quality and perceived value. This study applies a quantitative approach using an online questionnaire method to collect data from participants. The total population consists of all individuals living in Bandung City aged between 15 and 60 years. The sample size is 384 individuals who meet the required criteria. To assess the participants' views on the variables studied, a Likert scale was used. The statistical tool used is SPSS version 22. The findings of the analysis indicate that the level of customer satisfaction is significantly influenced by product quality. Such evidence is reflected in a significance value (Sig.) recorded at 0.000, positioned below the established threshold of 0.05, with the t-test results showing a figure of 7.415. In addition, the influence of perceived value on customer satisfaction is proven to be positive and significant, as indicated by the t-test results reaching 8.400 > t table 1.966, and supported by a significance level of 0.000 < 0.05. Furthermore, there is a simultaneous influence between product quality and perceived value on customer satisfaction with an F-test value of 299.317, which clearly exceeds the F-table limit of 3.02 with a significance of 0.000. This finding confirms that increasing customer satisfaction relies on two fundamental elements, namely product quality and perceived value.